Low-density lipoprotein cholesterol reduction with evolocumab and its use in clinical practice: evidence from Swedish national register data. (3rd October 2022) - Svensson, M K; James, S; Ravn-Fischer, A; Pantev, E; Villa, G; Schalin, L; Cars, T; Gustafsson, S; Hagstrom, E
Abstract: Background/Introduction: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors reduce low density lipoprotein cholesterol (LDL-C) levels by around 50% to 60%, and the risk of cardiovascular events in patients with atherosclerotic cardiovascular disease (ASCVD) in randomized clinical trials. Data on LDL-C reduction with PCSK9 inhibitors and its use in clinical practice is lacking. Purpose: Assess LDL-C reduction with the PCSK9 inhibitor evolocumab and its use in clinical practice in Sweden. Methods: Population-based, retrospective, longitudinal, observational study of patients initiating evolocumab treatment between July 2015 and May 2020. Patients undergoing lipoprotein apheresis were excluded. Patient level data was obtained from national diagnosis and pharmaceutical registers (covering 100% of the Swedish population), and electronic health records (covering 60% of the Swedish population). The use of evolocumab was assessed based on persistence with and adherence to treatment. Patients were defined as being persistent if they were still taking evolocumab 12 months after treatment initiation. Medication gaps were allowed until a last gap of ≥56 days. Patients were defined as being adherent if the proportion of days covered (PDC) by the drug was ≥80% during that same period. Mean LDL-C reduction was estimated 3 months after evolocumab treatment initiation, using a Generalized Least Squares regression model. Results: Overall, 2341 patients were included in the analysis, with a median follow-up of 376 days. Median age was 65 years, 43% were women, 79% had a history of ASCVD and, among them, 94% had had a coronary event and 24% had diabetes. 44% of the patients had LDL-C available. Median LDL-C was 4.1 mmol/L and 64% of the patients were receiving oral lipid-lowering treatment (LLT). After 12 months of treatment, 76% of the patients were persistent with evolocumab. In these patients, median PDC over 12 months was 93%, with 86% of these patients being adherent (PDC ≥80%). In the overall population (n=724), the estimated mean LDL-C reduction with evolocumab at 3 months was 48% (2.1 mmol/L, from 4.4 mmol/L at baseline). In patients who were adherent to evolocumab during the first 6 months (n=567), LDL-C reduction was 53% (2.2 mmol/L, from 4.3 mmol/L at baseline) (see figure). In patients who were adherent to both evolocumab and oral LLT (PDC ≥80% over a period of 3 months before and after evolocumab initiation) (n=186), LDL-C reduction was 59% (2.1 mmol/L, from 3.6 mmol/L at baseline). The estimated mean LDL-C reduction remained stable over a 6-month period. Conclusions: Persistence with and adherence to evolocumab treatment were high over 12 months. LDL-C reduction with evolocumab in clinical practice was similar to that observed in randomized clinical trials and remained stable over 6 months. At evolocumab treatment initiation, many patients had high LDL-C levels and underused oral LLT, potentially due to statin intolerance. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen